Navigating Sharia and Institutional Conflict: The Case of Land Pawning Practices in Aceh - Afna, Mauloeddin Afna (Jurnal Sosiologi Reflektif, 2024)
Sharia-based pawning practices in Aceh have long served as an important system for managing communal assets and fostering social cohesion. However, recent challenges, such as declining trust, rising gold prices, and misinterpretations of Sharia principles, have jeopardized the sustainability of this system. This study aims to explore the social, economic, and cultural dynamics that contribute to conflicts within Aceh’s pawning system, with a focus on how stakeholders address and resolve these conflicts. Employing a Participatory Action Research (PAR) approach, the study gathered data through literature reviews, interviews, and participant observation, involving local authorities, religious leaders, and community members. The research investigates how institutional logics—religious, cultural, and economic—shape conflict resolution strategies in the community. The findings indicate that while economic pressures and misapplications of Sharia principles drive these conflicts, successful resolution depends heavily on cooperation among stakeholders. The community’s role as mediator is critical in ensuring transparency, trust, and fairness. The study concludes that achieving a balance between Sharia compliance and local socio-economic realities is key to fostering sustainable reforms and ensuring the long-term stability of the pawning system in Aceh. Praktik gadai berbasis syariah di Aceh telah lama menjadi sistem penting dalam pengelolaan aset komunal dan memperkuat ikatan sosial. Namun, tantangan baru seperti erosi kepercayaan, kenaikan harga emas, dan penerapan yang salah dalam prinsip syariah telah mengancam keberlanjutannya. Penelitian ini bertujuan untuk mengkaji dinamika sosial, ekonomi, dan budaya yang berkontribusi terhadap konflik dalam sistem gadai di Aceh, dengan fokus pada cara para pemangku kepentingan menyelesaikan konflik tersebut. Penelitian ini menggunakan pendekatan Participatory Action Research (PAR) dengan mengumpulkan data melalui tinjauan literatur, wawancara, dan observasi partisipatif, melibatkan otoritas lokal, pemuka agama, dan anggota masyarakat. Studi ini mengeksplorasi bagaimana logika institusional—agama, budaya, dan ekonomi—membentuk strategi penyelesaian konflik di dalam komunitas. Hasil penelitian menunjukkan bahwa meskipun konflik dipicu oleh tekanan ekonomi dan penerapan yang salah prinsip syariah, penyelesaian yang efektif justru sangat bergantung pada kerja sama antara pemangku kepentingan. Peran komunitas sebagai mediator sangat penting dalam menjaga transparansi, kepercayaan, dan keadilan. Penelitian ini menyimpulkan bahwa keseimbangan antara kepatuhan terhadap syariah dengan realitas sosial-ekonomi lokal adalah kunci untuk menciptakan reformasi yang berkelanjutan dan memastikan kelangsungan jangka panjang dari sistem gadai di Aceh.